Entrepreneurship and innovation: citizenship status for engineers in the twenty-first century - Vera Castillo, Pedro (Ingeniería Solidaria, 2016)
It is common to associate entrepreneurship with a need —usually when something hard to face occurs— the loss of a job we considered stable and secure, often unexpectedly. Creating a business then becomes a way out, starting a business becomes a necessity. And then, we begin to think that everything we learned so far is no longer useful to face this new situation. This is because we were trained for a few decades, to have “a formal job that would last a lifetime”.